From guidelines to ground reality: Challenges faced by an infection control nurse for control of MDR infection in Nepal. - Thapa, Roshani; Birbal, Sabina; Shrestha, Pramesh Sunder (Journal of Nepalese Society of Critical Care Medicine, 2024)
Not available